Developing Speaking Skill through Oral Report in an EFL Class in Indonesia - Marzuki, Abdul Gafur (Institut Agama Islam Negeri Imam Bonjol Padang, 2017)
This Classroom Action Research aims at developing studentsâ speaking skill through the application of oral report technique. This research is conducted collaboratively in three cycles in which researcher acts as a lecturer while his collaborator acts as an observer and each cycle consists of two meetings. Data of this research is attained from two main sources namely qualitative and quantitative data. The data shows that In preliminary study, 35.5% students could answer questions given by researcher through interview but the achievement score shows that 13.3% students could fulfill the minimum criteria of achievement. The minimum criterion of achievement is 60. At cycle I, 37% students could participate in oral report and 24.4% students could fulfill the minimum criteria of achievement. At cycle II, 51.1% students could participate in oral report and 42.2% students could fulfill the minimum criteria of achievement. The last is 75% students could fulfill the minimum criteria of achievement from 86.6% students who participated in oral report at cycle III from 45 students. Furthermore, the highest score obtained by student from each of cycles present that in preliminary study is 70 whereas 72.5 at cycle I, 85 at cycle II, and 90 at cycle III. Based on the findings of this research, it can be inferred that the application of oral report technique can develop studentsâ speaking skill in using English